Safety and Benefit Of Sentinel Lymph Nodes Biopsy Compared to Regional Lymph Node Dissection in Primary Vulvar Cancer Patients Without Distant Metastasis and Adjacent Organ Invasion: A Retrospective Population Study - Zhou, Weili; Bai, Yang; Yue, Yangyang (Frontiers in Oncology, 2021)
Background: The safety and benefit of sentinel lymph node biopsy (SLNB) compared to regional lymph node dissection (RLND) and no lymph nodes removed (NA) in patients with vulvar squamous cell cancer (VSCC) was not well studied. Methods: A retrospective analysis on VSCC patients without distant metastasis and adjacent organ invasion from the Surveillance, Epidemiology, and End Results Program database between 2004-2016 was carried out. Within subgroups stratified by negative (LN-) or positive (LN+) regional lymph node findings, inverse probability weighting (IPW) adjusted multivariate Fine-Gray compete-risk (CR) model and accelerated failure time (AFT) model was used to investigate factors associated with and cancer-specific survival (CSS) and overall survival (OS). Results: Of the 3161 VSCC patients treated with surgery, 287(9.1%) underwent SLNB, 1716(54.3%) underwent RLND, and 1158 (36.6%) had no regional lymph nodes removed. As illustrated by IPW adjusted multivariate regressions, SLNB was significantly associated with prolonged CSS (LN-: adjusted sub-proportional hazard ratio [sHR]=0.42, 95% confidence interval [CI] 0.19-0.93, P=0.032; LN+: adjusted sHR=0.29, 95% CI 0.16-0.54, P<0.001) and OS (LN-: adjusted time ratio [TR]=1.38, 95% CI 0.82-2.32, P=0.226; LN+: adjusted TR=2.68, 95% CI 1.73-4.14, P<0.001), although the effect of SLNB on OS was not significant within the LN- cohort. Moreover, SLNB led to improved CSS (adjusted sHR=0.40, 95% CI 0.23-0.70, P=0.001) and OS (adjusted TR=1.15, 95% CI 0.76-1.73, P=0.279) compare to NA. Age was a significant prognostic factor of CSS and OS, while tumor size, surgery type, and invasion depth were not. Conclusions: SLNB leads to significantly prolonged CSS and OS in VSCC surgery patients without distant metastasis and adjacent organ invasion than RLND, except for the similar OS in the LN- cohort. SLNB could be carried out preferentially for VSCC surgery patients without distant metastasis and adjacent organ invasion, irrespective of tumor size, surgery type, invasion depth, and regional lymph nodes metastasis. Further prospective clinical trials are warranted to confirm the findings of this study.